2017
DOI: 10.21608/ajssa.2017.138408
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Standard Performance Scores and levels for battery of some basic skills tests in boxing for students at the Faculty of Physical Education

Abstract: This research aims to determine the standard performance scores and levels for battery of some basic skills tests in boxing for students at the Faculty of Physical Education. The researcher used (Rakha, 2016) battery to measure the basic skills in Boxing that involved in the course description of Boxing (1) for academic third level, Faculty of Physical Education in Port Said. The battery validity coefficient ranged between (0.945 -0.978) and the stability coefficient ranged between (0.887 -0.957) that indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This allowed learners to master these skills regardless of the teaching strategy used on them. This is consistent with previous studies such as [58,59].…”
Section: Plos Onesupporting
confidence: 94%
See 1 more Smart Citation
“…This allowed learners to master these skills regardless of the teaching strategy used on them. This is consistent with previous studies such as [58,59].…”
Section: Plos Onesupporting
confidence: 94%
“…Many previous studies have used these checklists on similar samples as the current study, including [58][59][60], which found that they had a validity coefficient of 0.97 and a reliability coefficient of 0.87.…”
Section: Plos Onementioning
confidence: 90%
“…This program aims to improve some of the fundamental defensive skills of junior boxers between the ages of 12 and 14. According to several studies [ 110 – 112 , 115 ], boxing juniors should have some fundamental defensive skills listed in Table 1 to defend themselves against straight punches.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies using similar samples have used this checklist. [23,[110][111][112] reported that it had a validity coefficient of 0.97 and a reliability coefficient of 0.87.…”
Section: A Checklist For Arbitrators To Evaluate the Fundamental Skil...mentioning
confidence: 99%
See 1 more Smart Citation